2017
DOI: 10.1074/jbc.m117.810127
|View full text |Cite
|
Sign up to set email alerts
|

Splice variants of cytosolic polyadenylation element–binding protein 2 (CPEB2) differentially regulate pathways linked to cancer metastasis

Abstract: The translational regulator cytosolic polyadenylation element-binding protein 2 (CPEB2) has two isoforms, CPEB2A and CPEB2B, derived by alternative splicing of RNA into a mature form that either includes or excludes exon 4. Previously, we reported that this splicing event is highly dysregulated in aggressive forms of breast cancers, which overexpress CPEB2B. The loss of CPEB2A with a concomitant increase in CPEB2B was also required for breast cancer cells to resist cell death because of detachment (anoikis res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 27 publications
4
37
0
Order By: Relevance
“…The ratio of A/B isoforms (ratios of mean of ΔCT) was higher in non-tumor tissues (Fig. 8a), supporting the reports that A is the tumor-suppressor isoform and B the tumor-promoter isoform [29, 30]. The information on ER, PR and HER2 status (n value) was available in 98 out of 105 samples as follows: 19 HER2+, 64 HER2-, 75 ER+, 18 ER-, 64 PR+, 29 PR-, 11 ER/PR/HER+ and 10 ER/PR/HER2-.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…The ratio of A/B isoforms (ratios of mean of ΔCT) was higher in non-tumor tissues (Fig. 8a), supporting the reports that A is the tumor-suppressor isoform and B the tumor-promoter isoform [29, 30]. The information on ER, PR and HER2 status (n value) was available in 98 out of 105 samples as follows: 19 HER2+, 64 HER2-, 75 ER+, 18 ER-, 64 PR+, 29 PR-, 11 ER/PR/HER+ and 10 ER/PR/HER2-.…”
Section: Resultssupporting
confidence: 86%
“…The roles of CPEB2 in human breast tumorigenesis have so far remained a paradox, until isoform-specific roles were identified [29, 30]. Selecting cells from TNBC cell lines for anioikosis-resistance, these authors observed that alternative splicing resulting in the loss of CPEB2A with concomitant increase in CPEB2B was responsible for their metastatic phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations